Quarkonium production at the LHC: A data-driven analysis of remarkably simple experimental patterns - Faccioli, Pietro; Lourenço, Carlos; Araújo, Mariana; Knünz, Valentin; Krätschmer, Ilse; Seixas, João (My University, 2017)
The LHC quarkonium production measurements reveal a startling observation: the J/$\psi$, $\psi$(2S), $\chi_{c1,2}$ and $\Upsilon$(nS) $p_{\rm T}$-differential cross sections are compatible with one universal momentum scaling pattern. Considering also the absence of strong polarizations of directly and indirectly produced S-wave mesons, we are led to the conclusion that there is currently no evidence of a dependence of the partonic production mechanisms on the quantum numbers and mass of the final state. The experimental observations supporting this universal production scenario are remarkably significant, as shown by a new analysis approach, unbiased by specific theoretical calculations of partonic cross sections, which are only considered a posteriori, in comparisons with the data-driven results.